Development of Smart Spirometer System for at-Home Post Covid-19 Patients - Ramaiya, Iswerya; Nurmiza Othman, (Evolution in Electrical and Electronic Engineering, 2023)
This project proposes the development of a smart spirometer system for at-home use by post-Covid-19 patients in order to address the need for long-term monitoring of pulmonary function during rehabilitation. The system is composed of a TCRT5000 infrared sensor, a Node MCU ESP8266 microcontroller, a YFS-201 flow meter sensor, and a Liquid Crystal Display (LCD) unit. The TCRT5000 infrared sensor is small and lightweight and can detect the presence of a ball while, the YFS-201 flow meter sensor measures the volumetric flow of the respiration rate and sends the data in the form of voltage to the microcontroller. The microcontroller converts the voltage value into digital form and displays the output through the LCD 16x2 display and the Blynk application. With the data provided, important physiological parameters such as air flow rate, QIO, and volumetric flow, V can be calculated. The final outputs of the project are Tidal Volume and Inspiratory Capacity Volume (in liter). This smart spirometer system provides a low-cost and convenient method for monitoring pulmonary condition during recovery from Covid-19.